2009
DOI: 10.1002/ca.20748
|View full text |Cite
|
Sign up to set email alerts
|

Normal renal arterial anatomy assessed by multidetector CT angiography: Are there differences between men and women?

Abstract: The purpose of this study was to determine renal arterial anatomy and gender differences in adults without renovascular disease using multidetector computed tomography angiography (MDCTA). MDCTA datasets of 399 patients were retrospectively reviewed. Measurements of the aortorenal diameters, the angulation of the renal ostia and pedicles as well as the distance between the origins of the renal arteries were measured. Differences in measurements between genders were tested for statistical significance using ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 17 publications
0
27
0
2
Order By: Relevance
“…Not all arteries are visualised due to their anatomic position, including CA, SMA and IMA [25,59]. Computerised topographic angiography and magnetic resonance angiography are precise, objective and repeatable [66,99] but method they apply (3-dimensional reconstruction of vessels filled with contrast material) is probably superior for lumen rather than diameter estimation. Also they are usually performed at diseased populations, are relative expensive and not widely available.…”
Section: Discussionmentioning
confidence: 99%
“…Not all arteries are visualised due to their anatomic position, including CA, SMA and IMA [25,59]. Computerised topographic angiography and magnetic resonance angiography are precise, objective and repeatable [66,99] but method they apply (3-dimensional reconstruction of vessels filled with contrast material) is probably superior for lumen rather than diameter estimation. Also they are usually performed at diseased populations, are relative expensive and not widely available.…”
Section: Discussionmentioning
confidence: 99%
“…The dilatation must be at least twofold in order to be considered an aneurysm [3]. According to a study enrolling adults without renovascular disease, the normal renal artery diameter is approximately 0.5 cm [4]. As it applies in other blood vessels, when this dilatation involves all the layers of the wall of the renal artery, the aneurysm is characterized true.…”
Section: Discussionmentioning
confidence: 99%
“…10 Recently, it was shown in a large cohort of patients undergoing CT-angiography that normal right and left renal arteries have a mean diameter of 4.8-4.9 mm, respectively. 11 More recently, Okada et al 12 reported about renal artery lumen diameters in 122 hypertensive patients with a mean renal artery lumen diameter of 5.9 ± 1.0 mm for the right renal artery and 6.1 ± 1.0 mm for the left renal artery. Therefore, we regarded renal arteries with a diameter of 4.8 mm or less as too narrow, indicating their small caliber.…”
Section: Small Caliber Renal Arteries In the Angiographymentioning
confidence: 99%